A new prediction method for the viscosity of the molten coal slag. Part 1: The effect of particle morphology on the suspension viscosity. (15th May 2018) - Zhou, Jie; Shen, Zhongjie; Liang, Qinfeng; Xu, Jianliang; Liu, Haifeng
Highlights: The influence of the particle morphology on the suspension viscosity was studied. The effect of particle size, shape and aspect ratio on viscosity were obvious. A new modified viscosity model of the suspension was obtained. Prediction results of modified viscosity model showed agreed with experimental data. Abstract: Viscosity is the key factor affecting the flowability of molten coal slag in the entrained flow gasifier. The volume fraction and morphology of solid phase in slag are important factors affecting the slag viscosity. In this study, the malt syrup and the particles with different sizes and morphologies were chosen as the simulation medium to study the effect of particle morphology on the suspension viscosity. The influences of size, shape and aspect ratio of solid particles on the suspension viscosity were considered. It was concluded that the suspension viscosity increased with the decrease of the particle size. The suspension viscosity increased with the increase of the aspect ratio of the particles. This phenomenon was more obvious under the high volume fraction of solid phase. With the same size and aspect ratio, the non-spherical particles had greater effect on the suspension viscosity than spherical particles. A correction factor was used to modify the viscosity model with the consideration of particle size, shape and aspect ratio. The prediction results of new modified viscosity model of the suspension finally showed good agreement with the measured experimental data.